Antecedents of IS infusion behaviours: an integrated IT identity and empowerment perspective. Issue 11 (18th August 2022) - Hassandoust, Farkhondeh; Techatassanasoontorn, Angsana A.
ABSTRACT: Organisations expect that users will fully incorporate information technology (IT) into their work to achieve the benefit of IT deployment in the post-adoption period. Evidence from previous research shows that these benefits are not determined by the initial use of technology but rather through usage behaviours with which individuals maximise the potential of the technology known as infusion behaviours. Drawing on IT identity and psychological empowerment theories, this study examines the influence of users' IT identity and empowerment on IS infusion behaviours and three qualitatively distinct usage behaviours associated with infusion: extended use, integrated use, and emergent use. A total of 344 survey responses were collected from enterprise systems users in New Zealand. The results suggest that IT identity and empowerment shape IS infusion and its three distinct associated behaviours. This study offers a deeper understanding of how strong identification with IT and psychological empowerment toward the use of IT in work routines are important drivers of IS infusion behaviours in organisations.